Pequenas empresas de semillas - Habich, GE (International Center for Tropical Agriculture, 1991)
A conceptual framework is given for the creation of small seed enterprises as a market alternative of diverse grains for small- scale, low-income farmers. Managerial aspects of small enterprises are discussed and special restrictions to be taken into account in the case of bean seed are analyzed. (CIAT)